2005
DOI: 10.1111/j.0735-2751.2005.00255.x
|View full text |Cite
|
Sign up to set email alerts
|

The Detraditionalization of Intimacy Reconsidered

Abstract: This essay challenges those strains of contemporary social theory that regard romantic/ sexual intimacy as a premier site of detraditionalization in the late modern era. Striking changes have occurred in intimacy and family life over the last half-century, but the notion of detraditionalization as currently formulated does not capture them very well. With the goal of achieving a more refined understanding, the article proposes a distinction between “regulative” and “meaning-constitutive” traditions. The former… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
171
0
12

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(187 citation statements)
references
References 52 publications
(24 reference statements)
3
171
0
12
Order By: Relevance
“…Individuals not subscribing to the traditional ideal constitute a heterogeneous minority, with diverse ideas about sexual behaviour and relationships that may in different instances resonate with feminist, queer theoretical, Giddensian, libertarian, or (some) 'traditional masculine' perspectives. However, while this minority mirrors contemporary lifestyle diversity, highlighting the decline of sexually exclusive co-residence as a regulative tradition (Gross, 2005), it is not apparently growing substantially, perhaps restricted by the resilience of certain normative ideas, e.g. regarding fidelity and parenting.…”
Section: Concluding Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Individuals not subscribing to the traditional ideal constitute a heterogeneous minority, with diverse ideas about sexual behaviour and relationships that may in different instances resonate with feminist, queer theoretical, Giddensian, libertarian, or (some) 'traditional masculine' perspectives. However, while this minority mirrors contemporary lifestyle diversity, highlighting the decline of sexually exclusive co-residence as a regulative tradition (Gross, 2005), it is not apparently growing substantially, perhaps restricted by the resilience of certain normative ideas, e.g. regarding fidelity and parenting.…”
Section: Concluding Discussionmentioning
confidence: 93%
“…Gross (2005) suggests that the detraditionalisation of intimacy in the US has involved a greater decline in the power of 'regulative traditions' than in the role of 'meaning-constitutive traditions'. Similarly, neither changes in behaviour nor changes in the forms of behaviour perceived as legitimate necessarily indicate a radical change in the ideals shaping (most) British people's behaviour.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…En este sentido, ya el mismo Max Weber (1972), al hilo de su teoría sobre el avance de la racionalización de las sociedades modernas, apuntó al amor erotizado como una de las "esferas de valores" que entran en competencia con la religión como fuente de sentido de la experiencia en un mundo crecientemente desencantado. Este argumento es recogido por otros autores que han analizado el amor en las sociedades contemporá-neas y que identifican en la vivencia subjetiva del mismo el acercamiento a lo sagrado que otros ám-bitos de las sociedades modernas secularizadas no pueden proporcionar (Beck y Beck-Gernsheim, 1998;Gross, 2005;Illouz, 2009) 6 . Esta construcción del sentido vital a través de la experiencia de los afectos amorosos y de las expectativas e ilusiones depositadas en él se hace más patente en la posición femenina, en la medida en que los modelos que enmarcan tal posición se construyen desde la primacía de los vínculos, por contraste con la autonomía que define el patrón hegemónico de masculinidad (García Selgas y Casado Aparicio, 2010: 122;Hernando, 2012).…”
Section: El Amor Como Promesa De Salvación Y Fuente De Identidadunclassified
“…This is perhaps most obvious in Zhang's paper where she argues for bringing western sociological concepts such as practices of intimacy and displaying family into dialogue with Chinese concepts of xiao and mianzi, thus following in the footsteps of others who have suggested that Chinese concepts may have broader sociological purchase (e.g., Qi 2014). All the papers, however, address the larger debates on processes of individualization and detraditionalization and their contested consequences for intimate relationships, which have been the subject of much debate in both western and Asian contexts in recent decades (Beck and Beck-Gernsheim 2002;Gross 2005;Heaphy 2007;Yan 2009;Chang and Song 2010;Jamieson 2011). All the papers indicate that it is unwise to think of these processes as either linear or universal.…”
mentioning
confidence: 99%